Characterization of Composite SiOx/Polymer Barrier Films. (21st November 2012) - Liu, Zhuang; Sun, Zhihui; Ma, Xinxin; Yang, Chun Li
Abstract : In this study, flexible polymer chains are incorporated into silicon oxide films by magnetron co‐sputtering two targets, namely, silica and dicyclopentadiene dioxide cured with maleic anhydride (DCPD/MA), to solve the brittle problems of these passive barrier packaging materials. Composite SiO x /polymer films are prepared on polyethylene terephthalate substrates by radio frequency (RF) reactive magnetron co‐sputtering to combine the flexible polymer groups in oxidation silicon coatings. The samples are prepared by changing the P DCPD / MA / P SiO 2, the RF power ratio delivered to the individual target, from 0.1 to 10. The barrier performance, mechanical properties and flexibility of the composite films are also investigated. The characteristics of the barrier differ from those of traditional passive packaging materials. Oxygen permeation measurements were carried out to verify the reasons for these differences and determine the structure of the films. The results showed that the active sites and double bonds existing in the composite films can scavenge oxygen and lengthen the lag time. Folding test results indicated that the composite films have much better flexibility than the SiO x films, which is attributed to the DCPD/MA segments incorporated into the composite films and the new bonds produced between SiO x and DCPD/MA, as proven by the Fourier transform infrared and X‐ray photoelectron spectroscope spectra analysis results. Tensile performance was improved significantly, and the trend of the stretch curves followed an approximate rule as the RF power ratio changed from 0.1 to 10. Moreover, two significant turning points in the stress–strain curves were observed as the films were stretched. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : The flexible polymer chains are incorporated into the silicon oxide films by magnetron co‐sputtering two targets, silica and dicyclopentadiene dioxide cured with maleic anhydride (DCPD/MA), which can solve the brittle problems of these passive barrier package materials. Folding test results indicate that the composite films have much better flexibility than SiO x films, which is attributed to DCPD/MA segments incorporated into composite films and the new bonds produced between SiO x and DCPD/MA.